MODELING OF ELECTRONIC STUDENT HEALTH RECORD FOR MONITORING STUDENT’S HEALTH BY COMMUNITY HEALTH CENTER, SCHOOL AND PARENTS IN INDONESIA (Proceedings of the International Conference on Public Health, 2021)
Schools regularly collect student health data. School health is organized to improve theability of students to live healthy so that students can learn, grow, and develop in harmony and becomequality human resources. In Indonesia, school health priorities are included in the 3rd NationalMediumTerm Development Plan strategy. However, in Indonesia students, health data is underutilizedbecause data documentation on paper causing some difficulties in terms of storage, use for monitoringand further analysis. The participation and involvement of parents, schools and community healthcenters in monitoring the health status of students today is still very limited due to the lack ofinformation that can be accessed easily. Objectives: To design a student health record applicationmodel that can display student health examination results and connect the data to community healthcenters, schools and parents in real time. Method: Designing student health record application modelwith the context diagram, Entity Relationship Diagram (ERD), Table Relational Diagram (TRD), anduser interface input and output. Results: The results of this study are a comprehensive student healthrecord system model. The student health record will be applied in the form of mobile devices used bystudents and parents, which are connected to schools and community health centers by web-basedplatform. Conclusions: The student health record application model shows a systematic solution thatis user friendly, immediately captures data, displays the dashboard in real time, directly connects toparents, schools and community health centers. All of this in the future if implemented properly canearly detect student health problems and monitor the health status of students.
Keywords: Student health record, real-time data, web-based application, dashboard, monitoring student’s health